PIF1-Interacting Transcription Factors and Their Binding Sequence Elements Determine the in Vivo Targeting Sites of PIF1. Issue 6 (14th June 2016) - Kim, Junghyun; Kang, Hyojin; Park, Jeongmoo; Kim, Woohyun; Yoo, Janghyun; Lee, Nayoung; Kim, Jaewook; Yoon, Tae-young; Choi, Giltsu
Abstract : In vivo PIF1 targeting to specific promoter sites is determined by PIF1-interacting transcription factors and their binding to G-box coupling sequence elements. Abstract: The bHLH transcription factor PHYTOCHROME INTERACTING FACTOR1 (PIF1) binds G-box elements in vitro and inhibits light-dependent germination in Arabidopsis thaliana . A previous genome-wide analysis of PIF1 targeting indicated that PIF1 binds 748 sites in imbibed seeds, only 59% of which possess G-box elements. This suggests the G-box is not the sole determinant of PIF1 targeting. The targeting of PIF1 to specific sites could be stabilized by PIF1-interacting transcription factors (PTFs) that bind other nearby sequence elements. Here, we report PIF1 targeting sites are enriched with not only G-boxes but also with other hexameric sequence elements we named G-box coupling elements (GCEs). One of these GCEs possesses an ACGT core and serves as a binding site for group A bZIP transcription factors, including ABSCISIC ACID INSENSITIVE5 (ABI5), which inhibits seed germination in abscisic acid signaling. PIF1 interacts with ABI5 and other group A bZIP transcription factors and together they target a subset of PIF1 binding sites in vivo. In vitro single-molecule fluorescence imaging confirms that ABI5 facilitates PIF1 binding to DNA fragments possessing multiple G-boxes or the GCE alone. Thus, we show in vivo PIF1 targeting to specific binding sites is determined by its interaction with PTFs and their binding to GCEs.